Therī therā rahantā pugguilʻ krīʺ myāʺ - Vannasīri, ʼA rhaṅʻ (ʼAṅʻ kraṅʻ Ripʻ Cā pe : Praññʻ luṃʺ kyvatʻ Phranʻʹ khyi rāʺthāna, Ca payʻ Ū̋, 1986)
Biographies of the early Buddhist monks and nuns from Burma; gleaned from the Theravada Buddhist canon.